PENGELOMPOKAN KECERDASAN ANAK DENGAN PENDEKATAN METODE FUZZY LOGIC - ., Syahminan (DINAMIKA DOTCOM, 2018)
Intelligence of children is an important thing to know the parents early on. Typing can be done with a childs intelligence classification dominant characteristics of each type of intelligence. To make it easier for parents in determining the type of childrens intelligence and how to overcome them, for it created a classification system kecerdasa intelligence grouping children by using fuzzy logic method for determination of a childs degree of intelligence type. From the analysis we concluded that the presence of intelligence classification systems pendekan children with Fuzzy Logic method of determining the type of the childs intelligence can be done in a way that is easier and the results more accurate conclusions than manual tests. Keywords: Classification, Intelligence, approach Fuzzy Logic.